Pandangan Paulus tentang bekerja yang professionaldalam 2 Tes 3: 10 dan aplikasinya bagi orang Kristen masa kini - Abatan, Yofince (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2025)
Work is an essential aspect of human life and is often associated with the pursuit of well-being. However, many fail to recognize that work is not solely oriented toward material fulfillment but also carries a significant spiritual dimension. This study aims to reveal the theological values of work based on 2 Thessalonians 3:10, which reflects the Apostle Paul's teaching on the responsibility of labor within the Christian faith. The research employs a literature study method with an exegetical approach to the text of 2 Thessalonians 3:10, focusing on the Greek verb ergazesthai, the infinitive form of ergazomai, which signifies working actively and responsibly. The findings show that although Paul does not explicitly use modern terminology such as "professional," his concept of work includes elements of skill, competence, commitment, precision, and dedication of time, effort, and thought. Paul emphasizes that work is a moral and spiritual obligation, not only to meet physical needs but also as a testimony of faith. This theological reflection affirms that Christians are called to work professionally, with integrity and a spirit of service, following the example set by Jesus Christ during His life.